Numerical Solution of the Reaction-Diffusion Equation (Journal of Computational Mathematics, 2021)
In this paper, we consider the numerical solution for the reaction-diffusion equation. A finite difference scheme and the basic error equality are given. Then the error estimations are proved for the periodic problem with $v(x,t)≥ 0$, the first and second boundary value problems with $v(x,t)≥ v_0＞0$, and for $v(U)≥ v_0›0$. Under some conditions such estimations imply the stabilities and convergences of the schemes.